Postharvest disease control efficacy of the polyene macrolide lucensomycin produced by Streptomyces plumbeus strain CA5 against gray mold on grapes - Kim, Jeong Do; Kang, Ji Eun; Kim, Beom Seok (Elsevier BV, 2020)
Microbial secondary metabolites have been a valuable source of antifungal compounds for the fungicide industry to develop plant disease control agents. In order to find natural antifungal compounds useful for the control of Botrytis cinerea causing postharvest gray mold, we screened microbial culture extracts and found the extract of Streptomyces plumbeus strain CA5 which was isolated from the soil sample of Chuncheon Province. The cell extract of CA5 strain markedly reduced the disease incidence of gray mold on grapes to a value of 22.2 % while the non-treated control showed 100 % disease incidence. The active ingredient (CASA) was identified from the cell extract of CA5 strain using a variety of chromatographic methods and spectroscopic analyses. The structure of CASA was determined to be the polyene macrolide lucensomycin. Lucensomycin showed inhibitory effects against the spores of B. cinerea at a concentration as low as 1 mg L-1 and completely inhibited gray mold development on grapes at a concentration of 100 mg L-1.